Przyczynek do dyskusji na temat prowadzenia badań na podstawie osobliwej macierzy kowariancji - Zając, Kazimierz; Kosiorowski, Daniel (A contribution to the discussion about studies on the base of singular covariance matrix, 2006)
The objective of the paper is to give into a consideration for the researchers some simple and an intuition appealing method of dealing with singular covariance matrix in economic surveys (e.g. we have more variables than observations). In the empirical studies conducted for Polish territorial units the presented method (among others) is used to verify the hypothesis stating that there is a relations between socio-economic and demographic development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1105, s. 127-141